1966
DOI: 10.3171/jns.1966.25.1.0045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mechanical Stresses on the Spinal Cord in Cervical Spondylosis

Abstract: HE brain stem and spinal cord, from a mechanical point of view, can be regarded as a single unit, securely fastened above and below. During movement, the cervical cord and its dural covering slide upwards and downwards no more than s or 3 mm. within the vertebral canal. Therefore, the cord adopts the length of the spinal canal. When the cervical spinal column is flexed (ventroflexed), the cervical spinal canal elongates and the cord is stretched and lengthened. Extension (dorsiflexion) of the cervical spinal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
101
2
6

Year Published

1966
1966
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(114 citation statements)
references
References 24 publications
5
101
2
6
Order By: Relevance
“…The spinal cord stretches with flexionextension. This principle was demonstrated in a classic study by Breig in which he examined the effects of spondylotic bars and positioning of the cervical spine on the spinal cord geometry and blood flow [7]. He demonstrated that extension of the cervical spine causes the cord to relax and shorten.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The spinal cord stretches with flexionextension. This principle was demonstrated in a classic study by Breig in which he examined the effects of spondylotic bars and positioning of the cervical spine on the spinal cord geometry and blood flow [7]. He demonstrated that extension of the cervical spine causes the cord to relax and shorten.…”
Section: Introductionmentioning
confidence: 98%
“…However, he also demonstrated that the vascular supply of the cord is an important consideration. The arterioles that branch from the anterior spinal artery may be subjected to mechanical compression with flattening of the cord in the sagittal plane leading to ischemia of cord [7]. These phenomena continue to be areas of active research and form much of our modern understanding of the pathogenesis of neuron damage in CSM mediated by both ischemic and mechanical insults to the cord.…”
Section: Introductionmentioning
confidence: 99%
“…
IntroductionReid [43,44] and Breig and colleagues [3,4], on the basis of a cadaveric study, hypothesized that spinal cord compression by the vertebral bodies and intervertebral discs during neck flexion caused cervical myelopathy. Later, the pincer mechanism of the cervical spine became emphasised, and neck extension was thought to be the predominant pathology of cervical myelopathy [41].
…”
mentioning
confidence: 99%
“…It is observed in 7.6-26% of asymptomatic subjects. 1,2 Numerous factors that contribute to the onset of cervical myelopathy have been reported, including intramedullary ischemia due to mechanical distortion of the spinal cord, 3 a pincer effect, 4 developmental canal stenosis, 5 watershed area of the spinal cord 6 and repeated minor trauma presumed by the pathophysiological similarity to solidtype spinal cord injuries. 7 However, biomechanical influence on the neural tissue damage remains inadequately understood.…”
Section: Introductionmentioning
confidence: 99%